AKTUALISASI NILAI PANCASILA DI ERA GLOBALISASI: TINJAUAN AKTUALISASI PANCASILA DALAM PENGGUNAAN TEKNOLOGI DI KALANGAN GENERASI MUDA - Aulia, Tita; Dewi, Dini Anggraeni (Universitas Tanjungpura, 2022)
Pancasila, as the nation's ideology and the guideline of the Indonesian people in the country and society, has become essential to every individual soul of Indonesian culture. Therefore the elaboration of Pancasila values as a form of actualization and realization of Pancasila values makes the creation of norms and laws a regulator of social life. Pancasila as an ideology has noble values that come from the soul of the Indonesian people themselves; therefore, the actualization of Pancasila values in generations. The current state of youth is a study that needs to be studied. The realization of the Pancasila values of Indonesia's young age is currently faltering and the rapid development of technology. This natural, technological development makes many positive and negative impacts on society and the state. The presence of technology can also threaten Pancasila as the nation's ideology by a new culture. Therefore, the actualization and understanding of Pancasila are very important for the integrity of the Indonesian country and state, especially among young people during this rapid globalization era.